Differences in phonologic and prosodic abilities in children with phonological language impairment and phonological-grammatical language impairment assessed with non-word repetition. (2nd April 2016) - From, Åsa; Sundström, Simon; Samuelsson, Christina
Abstract : Prosody can be described as the rhythmic, dynamic, and melodic aspects of language. Swedish has a relatively complex prosodic system compared to, for example, English. A large percentage of Swedish children with language impairment show prosodic problems to some extent. In the present study, non-word repetition was used to assess the phonological and prosodic abilities in children with phonological language impairment and children with phonological-grammatical language impairment. In the study, 10 children with phonological language impairment and 14 children with phonological-grammatical language impairment from 4;3 to 6;2 years of age participated. All children heard the same recorded non-words and words. The group with phonological language impairment received higher scores in all variables, compared to the group with phonological-grammatical language impairment. The results showed significant differences between the groups regarding production of vowels correct in words and production of phonemes correct in non-words as well as production of unstressed syllables in non-words and production of correct stress in non-words. Percent correctly produced vowels in words, but not in non-words, correlated significantly with grammatical ability.